2011
DOI: 10.1007/s12098-010-0351-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth, Puberty and Endocrine Dysfunctions in Relation to Iron Overload in Multi Transfused Indian Thalassemia Patients

Abstract: In this study analysis, short stature and hypogonadism were frequent findings. These results support the need for vigilant clinical evaluation of growth and puberty, as well as appropriate hormonal evaluation in poly transfused thalassemic children in order to detect and treat endocrine dysfunction early. The authors also recommend aggressive and adequate chelation from early life so that permanent damage to the endocrine glands can be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
2
22
0
2
Order By: Relevance
“…As a consequence of inadequate iron chelation, endocrine abnormalities like growth retardation and delayed puberty are well known in Indian thalassemics. 12 The situation was similar in our study at enrolment. What was striking was that, in the Jeevan Asha group, approximately 17.4% patients attained puberty with hormonal induction treatment within nine months, while only 3.8% of total pre-pubertal patients attained puberty in the control group during the same period where none of the patients could afford it.…”
Section: Discussionsupporting
confidence: 83%
“…As a consequence of inadequate iron chelation, endocrine abnormalities like growth retardation and delayed puberty are well known in Indian thalassemics. 12 The situation was similar in our study at enrolment. What was striking was that, in the Jeevan Asha group, approximately 17.4% patients attained puberty with hormonal induction treatment within nine months, while only 3.8% of total pre-pubertal patients attained puberty in the control group during the same period where none of the patients could afford it.…”
Section: Discussionsupporting
confidence: 83%
“…[3]. Harish et al, (2011); also was reported that minimal siderosis, with reduced number of primordial follicles, and thickened ovarian capsules was noticed in these patients [28].…”
Section: Discussionmentioning
confidence: 84%
“…Anemia and iron overload are responsible for endocrine dysfunction in β-thalassemia [2]. Though meticulous management has prolonged the life expectancy of these patients, they tend to suffer from growth retardation and endocrine dysfunction that are multifactorial in etiology and may be can't prevent by treatment [3]. If regular transfusion program is initiated to maintain the hemoglobin (Hb) level 9 -10 g/dl, normal growth occurs till the age of 10 -12 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypogonadism and abnormal spermatogenesis have been identified as primary causes of sexual dysfunction seen in β-thalassemia patients [100,102]. The hypogonadism-like symptoms are related to either anemia [103] or iron accumulation in the pituitary gland [104]. Treating infertile male patients with β-thalassemia with growth hormone and gonadotropins improved semen parameters [105].…”
Section: Male Reproductive Complications Associated With Iron and Copmentioning
confidence: 99%